1994
DOI: 10.2307/1937469
|View full text |Cite
|
Sign up to set email alerts
|

Soil Chemical Change during Three Decades in an Old‐Field Loblolly Pine (Pinus Taeda L.) Ecosystem

Abstract: The ability of soil to sustain its supply of nutrients to a growing forest is controlled by a complex of biogeochemical processes. Forest soil data are notably absent, however, that describe sustained nutrient supply of nutrient depletion. The objective of this study was to evaluate how exchangeable nutrient cations of a previously cultivated Ultisol responded to the first three decades of pine forest development. On six occasions during the three decades, the upper 0.6 m of soil was sampled from eight permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
107
1
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(127 citation statements)
references
References 38 publications
10
107
1
2
Order By: Relevance
“…Placement of lysimeters below the root zone is expected to capture soil solution samples that represent a loss to the system, although the presence of deep roots may pose a challenge to this assumption (52). The lysimeters used in this study were modeled after Richter et al (53): 3-in diameter polyvinyl chloride (PVC) pipe was sliced to create an opening with semiaxes of 10.16 and 5.08 cm. The pipe was lined with mesh, capped, and connected by tubing to a 1-liter high-density polyethylene (HDPE) collection bottle.…”
Section: Methodsmentioning
confidence: 99%
“…Placement of lysimeters below the root zone is expected to capture soil solution samples that represent a loss to the system, although the presence of deep roots may pose a challenge to this assumption (52). The lysimeters used in this study were modeled after Richter et al (53): 3-in diameter polyvinyl chloride (PVC) pipe was sliced to create an opening with semiaxes of 10.16 and 5.08 cm. The pipe was lined with mesh, capped, and connected by tubing to a 1-liter high-density polyethylene (HDPE) collection bottle.…”
Section: Methodsmentioning
confidence: 99%
“…Within the forest soil profile, concentrations of DOC are highest typically in the interstitial waters of the organic-rich upper soil horizons (McDowell and Likens, 1988;Richter et al, 1994;Dosskey and Bertsch, 1997). A significant portion of DOC is transported by the preferential flow, given that the state of adsorption equilibrium cannot be reached owing to the reduced contact time between DOC and the soil surface (e.g., Jardine et al, 1989;Hagedorn et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation structure can exert large influences on the light transmittance (Binkley and Giardina 1998;Richter et al 1994;Knops et al 2002), as well as on water and nutrients in ecosystems (Leuschner 2002). Several authors showed that dominating tree species in forests can greatly impact soil properties (Binkley and Giardina 1998;Knops et al 2002;Zhong and Makeschin 2004) or that different dominating plant species may have significant effects on environmental conditions, e.g.…”
Section: Introductionmentioning
confidence: 99%